Gray Level Histogram Analysis of Ultrasonic Images on a Microcomputer Based System. - DaPonte, John S.; Fox, Martin D. (IEEE, 1987)
Recent developments in image digitization have made possible a more quantitative analysis of ultrasonic imagery of the liver, which could lead to a more sensitive method for changes in liver texture as an aid in the diagnosis of liver disease. The approach described is the statistical analysis of one-dimensional intensity (gray-level) histograms obtained from B-mode ultrasonic images. First-order statistical parameters are used to characterize the location, variability, skewness and kurtosis of the histograms. One typical normal study and one typical abnormal study are presented to shown the type of results that have been obtained.
Keywords: ACOUSTIC IMAGING - Medical Applications; B-MODE ULTRASONIC IMAGES; BIOMEDICAL ENGINEERING - Imaging Techniques; GRAY LEVEL HISTOGRAM ANALYSIS; IMAGE PROCESSING; LIVER IMAGING; ULTRASONICS - Imaging Techniques; dept.csc; ⛔ No DOI found

Nonlinear Analysis of a New Sine Wave Oscillator. - Elahi, Ataollah; Guyton, Robert D. (IEEE, 1987)
A new type of RC op oscillator has been designed. For amplitude stabilization, diodes are added in the feedback of the linear circuit. A model has been developed for a nonlinear element, which affects the frequency of oscillation. The model can be used to design the oscillator for different frequencies and to calculate frequency and amplitude sensitivity with respect to the parameter of the system.
Keywords: NONLINEAR ANALYSIS; OSCILLATORS; RADIO EQUIPMENT; SINE WAVE OSCILLATOR; dept.csc